Peningkatan Pemasaran bagi Pengusaha Mikro Alat Permainan Edukatif (APE) di Daerah Istimewa Yogyakarta - Flourensia Septy Rahayu; Susi Widjajani; Wilfridus Bambang Triadi (Jurnal Maksipreneur, 2015)
Community service activity aims to increase knowledge for partners in terms of better product quality, and developing marketing strategies. Partners are selected on service activities are perpetrators unit small and medium businesses that have an interest in particular on the pattern of development of the child, by creating APE making industry, namely Dolanan Puzzles and Boneka Tangan Kang Bedjo. Approaches will be used to implement solutions to the problems that arises is the Virtual Store System development activities, counseling, training and mentoring. From the aspect of business management trying addressed is the problem of product marketing. The solution implemented is in the form of extension of the marketing strategy, the use of the Internet for marketing activities, and training in the use of Internet technology to marketing activities by utilizing tokopedia.com and Instagram. This addition was built 2 pieces online site for the 2nd partners as a means to market their respective products. After completion of development, partners can be trained to operate the site. Assistance activities carried out as a means of monitoring the results of education and training that have been obtained previously.